Microvascular Anastomosis in Practice: A Pilot Study on Microsurgical Training Efficiency - Florin-Vlad Hodea; Andreea Grosu-Bularda; Andrei Cretu; Catalina-Stefania Dumitru; Vladut-Alin Ratoiu; Eliza-Maria Bordeanu-Diaconescu; Raducu-Andrei Costache; Razvan-Nicolae Teodoreanu; Ioan Lascar; Cristian-Sorin Hariga (Clinics and Practice)
Background: Microsurgery is a demanding surgical field requiring precision and extensive training. There is a continued need for standardized training models to improve skill acquisition and efficiency in microvascular anastomosis. Objectives: This study aimed to assess whether a standardized microsurgery training protocol, focusing on technique-specific objectives, improves performance among beginner trainees. Material and Methods: A three-month, non-randomized cohort study was conducted with entry-level plastic surgery residents. Participants were assigned to either a control group, practicing without structured guidance, or a test group, using a predefined microsurgery curriculum. Skill performance was measured at baseline, three weeks, and three months using a modified University of Western Ontario Microsurgical Skills Assessment (UWOMSA) tool. Results: While both groups improved over time, the test group demonstrated significantly greater improvement at the three-month mark (mean score: 59 vs. 38; p = 0.00027). The structured training model promoted more consistent progress and superior microsurgical technique. Conclusions: A standardized training protocol significantly enhances microsurgical proficiency over time. These findings suggest value in structured, low-cost training models for microsurgical education. Limitations include the small sample size, use of non-living models, and a non-randomized design.